Auditoría de Gestión a la compañía de transporte escolar “Entre Ríos” S.A. de la ciudad de Loja, período 2021 - Astudillo Cobos, Alex David (2023)
The Curricular Integration Work called: Management Audit to the transport company "Entre Ríos" S.A. of the city of Loja, period 2021, was developed in compliance with the objectives aimed to evaluate the internal control system of the company, apply indicators to measure the efficiency, effectiveness and economy of management, finally prepare the audit report, containing the appropriate recommendations in order to improve the operations carried out by the company. The management audit was executed based on the five phases, starting with the general knowledge of the company's activities, information necessary for the planning of the audit, determining the objectives and procedures applied in the execution, which allowed to specify the findings that were supported with evidence obtained considering the characteristics of relevant, sufficient and competent. In the communication of results, the final report was issued in which the comments, conclusions and recommendations were established so that they can be adopted by the authorities to contribute to the development of the entity and finally to carry out the timely follow-up of such recommendations. The methodology used in the management audit consisted of the application of scientific research methods for the analysis and collection of theoretical content; deductive was used in the analysis of current regulations; inductive was used in the study of the information collected; analytical for the verification of the most relevant facts; synthetic to make the narrative sheets of the Curricular Integration Work, and mathematical was used in the development of management indicators and the use of techniques such as observation, analysis of information, surveys and interviews to determine the existing reality in the company. Among the most important results of the performance of the management audit, it can be mentioned that the company does not control the punctuality of attendance to the meetings of the General Shareholders' Meeting; it was also evidenced that the Board of Directors has not evaluated the remuneration of the main executives of the company; Fines assigned to shareholders for non-attendance at the General Shareholders' Meeting have not been collected; and, from the application of management indicators, it was determined that the routes assigned to shareholders for employee tours with public institutions were carried out in their entirety.